Assessing educational outcomes in South Africa relative to economically comparable countries: A comparative analysis - Nyamunda, John (South African journal of education, 2024)
The quality of education is a predictor of a country’s economic performance – which is why comparative international education surveys are important. South Africa performed poorly in the Trends in International Mathematics and Science Study (TIMSS) in 2019. The score of 374 for mathematics and 324 for science is poor compared to the mid-point of 500 and the performance of other upper middle-income countries that participated in the TIMSS 2019 survey. Research indicates that the country’s education performance is driven by a few key drivers. The aim with this study was to compare whether some of these key education performance drivers predicted performance of participating countries which are economically similar to South Africa. Only countries within one standard deviation of South Africa’s per capita GDP were selected. The results show that factors such as instructional time, learner-teacher ratios and language diversity were very strong predictors of performance in the 2019 TIMSS survey, with correlations of more than +/-0.80. While some factors are structural and cannot be changed (language diversity, for example) and others are very expensive to implement (reducing learner-teacher ratio), I propose the improvement of education outcomes through focusing on cost-effective impactful approaches. These are using student teachers to reduce the learner-teacher ratio in poor schools, making home language compulsory in homogeneous mother tongue areas, better management of instructional time and improving teachers’ continuous professional development in the short term.